Red fluorescence of Interdental plaque for screening of gingival health - Guk, Hye-Jin; Lee, Eun-Song; Jung, Ui-Won; Kim, Baek-Il (Photodiagnosis and photodynamic therapy, 2020)
•QLF technology can be a useful tool for detecting plaque pathogenicity as red fluorescence.•Red fluorescence of interdental plaque increased as the gingival inflammation worsened.•Red fluorescence of interdental plaque can be used as a potential indicator of gingivitis. Pathogenic dental plaque with deteriorated bacterial homeostasis around the gingival margin induces gingivitis. This study evaluated the applicability of red fluorescence (RF) properties of interdental plaque in screening for gingival health status. This cross-sectional study examined 178 teeth of 40 healthy subjects who had not lost both their first and second molars in at least one quadrant. Three groups (healthy, gingivitis, and periodontitis) were identified based on the periodontal health status (bleeding on probing, probing depth, clinical attachment loss) and plaque accumulation level (plaque index) in the interdental site between the first and second molars was evaluated. This interdental plaque between the first (distal surface) and the second molar (mesial surface) was collected using dental floss. A quantitative light-induced fluorescence (QLF) technology was used to assess RF emitted from the interdental plaque. The RF properties of the interdental plaque were quantified by fluorescence intensity (R/G value) and area (%). The RF variables were compared between the groups. The RF variables of the interdental plaque (R/G value and area) were significantly higher in the gingivitis and periodontitis group compared to the healthy group (p<0.0001, p=0.001), but there was no significant difference between the gingivitis and periodontitis groups. Significant correlations were identified between R/G value and bleeding on probing (r = 0.49, P < 0.01) and between R/G value and visual plaque index (r = 0.59, P < 0.01) for each tooth. Interdental plaque obtained by flossing and its red fluorescence quantified by QLF technology could be used as a potential indicator of gingivitis.